2014
DOI: 10.2298/aci1401051n
|View full text |Cite
|
Sign up to set email alerts
|

Complications associated with Percutaneous nephrolitholapaxy (PCNL): Our experience and literature review

Abstract: Reporting of complication for PCNL should be uniform, and modified Dindo-Clavien grading system that is validated for PCNL should be accepted to be a standard in urology. Surgeons training and experience are the most important to ensure the efficacy of procedure, therefore we suggest that learning of percutaneous renal access should be mandatory in residents trainee program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Complication rates for PCNL range from 20 - 83% ( 14 ). There is a need for standardized reporting of complication after PCNL ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates for PCNL range from 20 - 83% ( 14 ). There is a need for standardized reporting of complication after PCNL ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference between group A 20% and group B 22%. Nikić P et al [ 21 ], Tzeng et al [ 25 ], and Wang et al [ 26 ] showed similar results.…”
Section: Discussionmentioning
confidence: 70%
“…Mousavi-Bahar SH et al [ 8 ] reported 6% incidence of intraoperative bleeding. Nikie P et al [ 21 ] also reported 7.9% of intraoperative bleeding. Both studies had higher incidence of bleeding than screwed sheath group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of bacteremia after this intervention is 23%, of endotoxemia 34%, febrile reactions 25% and sepsis 0.3-2.5% [29]. One study showed that the overall complication rate after this procedure was 30% and that the most common complications observed were postoperative fever (9.52%) and bleeding [30]. A study involving 580 patients showed that three key factors correlated with the occurrence of sepsis.…”
Section: Interventions On the Urogenital Systemmentioning
confidence: 99%